The Influence Of Service Quality, Price And Promotion On Purchasing Decision In Go Ride (Gojek) Service - Elsa Niarawati; Kartini Istikomah; Deden Kurniawan; Yuphi Handoko Suparmoko (Asosiasi Dosen Muda Indonesia, 2025)
This research aims to analyze the influence of Service Quality (X1), Price (X2) and Promotion (X3) on Purchasing Decision (Y) of Go Ride customers in South Jakarta. Furthermore, instrument used research is questionnaire, then processed through SPSS 22.0 with several test conducted namely, data quality test, classical assumption test, multiple regression analysis and hypothesis testing. Meanwhile, the amounts of participations in this study were 120 respondents using purposive sampling method with population the customer of Go Ride that are living in South Jakarta. Conclusion is obtained through T-test that indicate Service Quality have significant influence on Purchasing Decision as partially. Price have significant influence on Purchasing Decision as partially. Promotion have significant influence on Purchasing Decision as partially.